Pertamina Energy Marketing Strategy and its Effect on Environment Performance - Trusnawati, Nana; Nursiti, Nursiti; Navanti, Dovina (International Review of Management and Marketing, 2019)
The purpose of this study is to explore whether the Pertamina Energy marketing strategy has a positive effect on environment performance. In addition, we also verify whether Pertamina Energy marketing strategy was seen from IFAS and EFAS analysis, so we could find out the competitive position of the Pertamina Energy. The methods of this study are mix methods. A SWOT analysis was the main method used for qualitative in this study and path analysis for quantitative methods. The empirical data were obtained from the Pertamina Energy Marketing Strategy Survey (PEMSS). Regarding the research results, in addition to Pertamina Energy marketing strategy proved to have a positive and significant effect on environment performance, Marketing Strategy Implications on Pertamina Energy based on indicators that are the strengths and opportunities of Pertamina Energy in the future, then an adequately applied marketing strategy is an intensive strategy with market penetration that is marketing to a wider market. Keywords: Pertamina Energy, Marketing Strategy, IFAS, EFAS, environment performance. JEL Classifcations: E6, Q430, Q470, Q480 DOI: https://doi.org/10.32479/irmm.8024